1999
DOI: 10.1051/aas:1999127
|View full text |Cite
|
Sign up to set email alerts
|

The Medicina survey of methanol masers at 6.7 GHz

Abstract: Abstract. A survey of Class II methanol masers at 6.7 GHz was made in the Northern hemisphere with the 32-m Medicina radio telescope. 42 objects were detected, 20 of them are new detections at 6.7 GHz. Our results show that the detection rate of 6.7 GHz masers toward the inner part of the Galaxy is higher than in other directions. It is confirmed that most of the methanol masers are associated with faint compact HII regions. The 6.7 GHz methanol masers show large velocity dispersion and large velocity offset f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
122
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 29 publications
16
122
2
Order By: Relevance
“…Brand et al (1994) also detected H 2 O masers from this source at similar radial velocity and flux density. Slysh et al (1999) did not find any 6.7 GHz class-II methanol maser emission from this region at a 3σ sensitivity of 3 Jy suggesting that the YSOs here may be very young. Codella & Felli (1995) did not detect any H89α hydrogen recombination line emission from IRAS 07422 suggesting that this source is very young and has not yet formed a diffuse Hii region.…”
Section: Introductionmentioning
confidence: 57%
“…Brand et al (1994) also detected H 2 O masers from this source at similar radial velocity and flux density. Slysh et al (1999) did not find any 6.7 GHz class-II methanol maser emission from this region at a 3σ sensitivity of 3 Jy suggesting that the YSOs here may be very young. Codella & Felli (1995) did not detect any H89α hydrogen recombination line emission from IRAS 07422 suggesting that this source is very young and has not yet formed a diffuse Hii region.…”
Section: Introductionmentioning
confidence: 57%
“…Four more masers were observed in the direction of IRAS sources that heve characteristics similsr to UC H ii regions, by Szymczak et al (2000) and Slysh et al (1999). Because of the relatively poor positional accuracy of IRAS, the positions of these masers are rather uncertain.…”
Section: Other Signposts Of Massive-star Formationmentioning
confidence: 99%
“…Slysh et al (1999) find that in those sources where 6.7 and 44 GHz masers coexist, the ratio of their flux density can be used to discriminate class I from class II masers. On the other hand, no correlation was found when comparing 6.7 with 12.2 GHz counterparts, except for the clear fact that 6.7 GHz masers are always found to be stronger in flux and in brightness temperature when assuming a constant source size (Malyshev & Sobolev 2003).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Slysh et al (1999) found that methanol masers show a clear velocity difference relative to the velocity of the parent cloud (a comparison made with the velocity of CS). This could suggest an origin for methanol masers in discs seen edge-on.…”
Section: Introductionmentioning
confidence: 99%